2020
DOI: 10.1212/wnl.0000000000008902
|View full text |Cite
|
Sign up to set email alerts
|

Early deviation from normal structural connectivity

Abstract: ObjectiveStudies of outcome after traumatic brain injury (TBI) are hampered by the lack of robust injury severity measures that can accommodate spatial-anatomical and mechanistic heterogeneity. In this study we introduce a Mahalanobis distance measure (M) as an intrinsic injury severity measure that combines in a single score the many ways a given injured brain's connectivity can vary from that of healthy controls. Our objective is to test the hypotheses that M is superior to univariate measures in (1) discrim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 19 publications
0
35
0
Order By: Relevance
“… Young et al., 2018 ). A key implication of such trajectories is that different brain processes (or disorders) may cluster in terms of their trajectories, or share parts of their trajectories, potentially indicating shared drivers/pathways/modulations ( Jensen, Moseley, Oprea, Ellesøe, Eriksson, Schmock, Jensen, Jensen, Brunak, 2014 , Taylor, Moreira da Silva, Blamire, Wang, Forsyth, 2020 ). Especially with a comprehensive region-specific and cross-region analysis of cortical morphology we expect clusters of directions to emerge.…”
Section: Discussionmentioning
confidence: 99%
“… Young et al., 2018 ). A key implication of such trajectories is that different brain processes (or disorders) may cluster in terms of their trajectories, or share parts of their trajectories, potentially indicating shared drivers/pathways/modulations ( Jensen, Moseley, Oprea, Ellesøe, Eriksson, Schmock, Jensen, Jensen, Brunak, 2014 , Taylor, Moreira da Silva, Blamire, Wang, Forsyth, 2020 ). Especially with a comprehensive region-specific and cross-region analysis of cortical morphology we expect clusters of directions to emerge.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the Mahalanobis distance provides information over and above a univariate analysis. In a study of patients with traumatic brain injury, (Taylor et al, 2020) demonstrated that the Mahalanobis distance derived from FA values of 22 white matter tracts better distinguished patients from controls (AUC = 0.82) than any individual univariate tract z-score (AUC = 0.72), and was associated with a level of cognitive impairment. A study of patients with autism demonstrated that the Mahalanobis distance could better distinguish patients from controls (Dean et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesised that patients with a longer epilepsy duration would be associated with greater abnormalities ipsilateral to the epileptic focus. This approach has been fruitful in studies of autism and traumatic brain injury (Dean et al, 2017;Taylor et al, 2020). Applications of the Mahalanobis distance include analysing individual tracts by integrating multiple diffusion metrics into a single measure, or by pooling numerous metrics from a number of different modalities.…”
Section: Introductionmentioning
confidence: 99%
“…The Mahalanobis distance, M, is a multivariate quantification of distance that, unlike Euclidean distance, considers the correlation between the variables (Figure 1A). As described in Taylor et al (2020), we computed the Mahalanobis distance of the edges in a bin for a patient, M, using the following:…”
Section: Hippocampal Network Change In Patientsmentioning
confidence: 99%